Nonlinear vibration control of a tall structure with tuned liquid column damper. Issue 2 (1st February 2016) - Lin, Shueei-Muh
ABSTRACT: The nonlinear vibration model of a structure with the tuned liquid column damper (TLCD) is established. TLCD is a successful structure control device. The damping of TLCD is amplitude-dependent and consequently nonlinear. Due to its complexity, the effective linear model is considered for investigating structure characteristics in almost all literatures. Moreover, the structure is usually modeled as a single degree of freedom model. However, the analytical solution for this nonlinear system is derived here. Further, it is found that the optimum design of TLCD for the suppression of vibration depends greatly on the structure parameters.